Denotative, Connotative, and Myth in The Nun Ii: A Semiotic Analysis of Supernatural Communication in Religious Horror Cinema - Nizmawati Amran; Kartin Lihawa; Usman Pakaya (Universitas Islam Negeri Palopo, 2026)
This study analyzes the denotative, connotative, and mythical meanings embedded in the communication between human characters and supernatural beings in The Nun II (2023), a religious horror film produced by Warner Bros. Pictures as part of The Conjuring Universe. Employing Roland Barthes' semiotic theory as the primary analytical framework, this research adopts a qualitative descriptive method to examine twenty selected scenes from the film. Data were collected through systematic observation and documentation of visual symbols, dialogues, sound effects, and cinematic elements. Analysis was conducted across three levels of signification: denotation, connotation, and myth. At the denotative level, the film presents literal depictions of supernatural phenomena, including possessions, apparitions, whispers, distorted religious symbols, and sacred relics. At the connotative level, these signs acquire culturally constructed meanings associated with spiritual vulnerability, divine protection, fear, and moral resistance. At the mythological level, the film systematically naturalizes the ideological belief that religious faith constitutes the ultimate power against supernatural evil. The findings reveal that possession functions as the most recurrent semiotic strategy, reinforcing the ideological message that spiritual weakness renders humans susceptible to demonic influence. Binary oppositions—light versus darkness, silence versus sound, isolation versus community—structure the film's entire semiotic system and consistently resolve in favor of divine authority. Furthermore, the inversion of the nun's sacred image into a demonic figure constructs a powerful mythological statement about the corruption of sanctity. This study concludes that The Nun II functions not merely as entertainment but as a culturally coded text that disseminates religious ideology through cinematic signs. The research confirms the continued relevance of Barthes' semiotic theory in analyzing ideological meaning-making within contemporary popular media.